Philosophical and distinct SLE epitomes: dogmas in conflict with evidences and an intellectual dissonance between established pathophysiological models - Rekvig, Ole Petter (Frontiers in Immunology, 2025)
This study centers around dogmas, their identifications and definitions, and their impact on our understanding of what Systemic lupus erythematosus (SLE) is. A focus is centered on description of how we investigate this enigmatic syndrome, and how we try to describe processual elements that can be targeted by experimental therapy modalities. Mostly, this study deals with definitions and critical insight into how dogmas hinder our understanding of SLE. When we start to investigate apparently convincing statements related to SLE, it is surprising how many of them are uncovered as authoritative, but not founded by concrete evidence! This problem refers to a definition of a dogma: A point of view or tenet put forth as authoritative without adequate grounds or evidence (Merriam-Webster). For example, several central statements/criteria are revealed as dogmas that challenge our insight into SLE as a complex syndrome. Critical in this context is the immense impact of “SLE classification criteria” versions in relation to evidence-based basic SLE processes. The SLE classification criteria will, as described in this study, most probably not identify SLE as “a one disease entity,” but more likely as a “poly-causal, poly-etiological, and poly-phenotypic “theoretical template SLE,” “SLE-like,” or “SLE-like non-SLE” syndromes. This is problematic as SLE may, in context of definitions described here, not be rationally structured by classification criteria. This prevents SLE cohorts from being suitable and ideal as study objects aimed to investigate experimental therapy modalities, genetics, etiology, and pathophysiology. However, this pessimistic view may turn into optimism if dogmas described in this study are identified and subjected to causal studies based on critical hypotheses. Today’s interpretative use of SLE classification criteria tentatively maintains a narrative that describes scientific studies of the SLE syndrome as not optimal and not ideal.